From Order to Chaos 2 (World Scientific Series on Nonlinear Science, Series a, Monographs and Treatises - P.Kadanoff Leo (World Scientific, 1998)
A compilation of review papers, exposition and technical works of Leo Kadanoff, a theoretical physicist, the aim of this text is to provide not-too-technical writing in which he discusses some issues in condensed matter physics, hydrodynamics, applied mathematics and national policy. The book is divided into five sections. The first section contains review papers on hydrodynamics, condensed matter physics and field theory. Next is a selection of papers on scaling and universality, particularly as applied to phase changes. A change of pace is provided by a series of papers on the critical analysis of simulation models or urban economic and social development. The book concludes with a series of recent papers on complex patterns. Each major section has an introduction designed to tie the work together and to provide perspective on the subject matter.